2013
DOI: 10.1111/jocn.12511
|View full text |Cite
|
Sign up to set email alerts
|

Constipation – prevalence and incidence among medical patients acutely admitted to hospital with a medical condition

Abstract: The study highlights the need to develop both clinical guidelines towards treating constipation, and preventive measures to ensure that patients do not become constipated while staying in hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…We also detected a significant increase in senna use in both non-frail and frail patients after warfarin initiation. Constipation is a common problem in hospitalised elderly patients [41]. Senna increases bowel motility thereby potentially decreasing the absorption of vitamin K and resulting in elevated INR values [42].…”
Section: Discussionmentioning
confidence: 99%
“…We also detected a significant increase in senna use in both non-frail and frail patients after warfarin initiation. Constipation is a common problem in hospitalised elderly patients [41]. Senna increases bowel motility thereby potentially decreasing the absorption of vitamin K and resulting in elevated INR values [42].…”
Section: Discussionmentioning
confidence: 99%
“…Using the strategy of wait and see and considering constipation a private challenge may also be related to not having discussed this issue during hospitalization. Other studies have found that prevalence and incidence are high, and often health-care professionals do not act until the problems are severe (Cardin et al, 2010 ; Noiesen et al, 2014 ; Rasmussen & Pedersen, 2010 ). On the one hand, this may be due to the fact that constipation remains difficult to talk about for both the patient and the nurse, like other bowel symptoms (Bliss et al, 2005 ; Cichowski et al, 2014 ) or other issues such as sexuality (Farrell & Belza, 2012 ) and spirituality (Molzahn & Sheilds, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified symptoms of constipation in 44% of patients being admitted acutely to medical care unit. Furthermore, among those patients with no symptoms, 51% developed signs of constipation during the first 3 days of their hospital stay (Noiesen et al, 2014 ). Experiencing constipation during hospitalization tend to exacerbate the general well-being of the patients as well as prolonging the hospital stay (Harari, Martin, Buttery, O'Neill, & Hopper, 2007 ; Rasmussen & Pedersen, 2010 ; Trads & Pedersen, 2015 ).…”
mentioning
confidence: 99%
“…Of these older people, 43% developed signs of constipation during the first three days of their hospital stay (Noiesen et al . ).…”
Section: Introductionmentioning
confidence: 97%